Taskforce of risk assessment for food safety in Vietnam: Linking science to policy to increase food safety and livelihood generation of the poor farmers - Hung Nguyen-Viet (2013)
One way capacity for risk assessment could be strengthened is through a Risk Assessment Task Force, bringing together representatives from Ministry of Health and Ministry of Agriculture and Rural Development with researchers in Vietnam working on risk assessment and food safety from key universities, research institutes, and private food companies. The Task Force will work on developing guidelines for how to use risk assessment for food safety management in informal markets for domestic consumption. These guidelines will be used for trainings for a wide range of decision makers, including high level policy makers. A technical-level course and case studies on food safety from informal markets will be used to increase risk assessment capacity for implementers, followed by mentoring and on-the-job support. Support from international and regional research institutes, such as ILRI, IFPRI, CENPHER, and international bodies such as WHO and FAO are already in place.